PERBEDAAN KADAR HEMOGLOBIN DAN INDEKS ERITROSIT PADA PASIEN GAGAL GINJAL KRONIK PRE DAN POST HEMODIALISIS DI RSPAL Dr. RAMELAN SURABAYA - Rut Jusrena Marweri; Evy Ratnasari Ekawati; Setyo Dwi Santoso (Jurnal SainHealth, 2022)
Chronic Kidney Disease can cause a progressive decline in kidney function which can lead to kidney failure. One of the therapies for patients with chronic kidney failure is hemodialysis, but this method can cause complications, including worsening of anemia. This study aims to determine differences in hemoglobin levels and erythrocyte index in patients with chronic renal failure before and after hemodialysis. This study is an experimental using data on hemoglobin and erythrocyte index results pre and post hemodialysis in patients with chronic kidney failure undergoing hemodialysis therapy at RSPAL dr. Ramelan Surabaya. Paired Sample T-test was used to determine differences in hemoglobin levels and erythrocyte index in patients with chronic renal failure pre and post hemodialysis. In this study, there were differences in hemoglobin levels and erythrocyte index in patients with chronic renal failure before and after hemodialysis.